Nazwy restauracji w łódzkim Orientarium proponowane przez internautów a współczesne tendencje onimiczne - Burska, Katarzyna (Papers in Linguistics, 2023)
The aim of the article is to verify which contemporary onymic tendencies of marketing chrematonymy can be seen in the names of restaurants submitted to the competition for a restaurant name in the Łódź Orientarium organized on the city’s official Facebook profile in February 2022. The research base is 1,200 naming creations. The following names can be distinguished in the analyzed material: those referring to the place where the restaurant is to be located; those based on vocabulary from the semantic field ‘food’; those highlighting locality; those pointing to the owner of the restaurant; those using broadly understood cultural connotations, as well as names-postulates thanks to which the Internet users manifested their views. The proposals lacked examples that would illustrate the interior design or characterize the owner, there were only few referring to specializing in a specific cuisine or dishes served. Many names contained positive evaluation. The Internet users applied all possible formal methods of creating onyms, i.e. transonymization (adding new lexical meaning to words), onymization (turning generic names to proper names), and also used new words and word combinations.